2018
DOI: 10.1017/s0007485318000299
|View full text |Cite
|
Sign up to set email alerts
|

Chinese chives and garlic in intercropping in strawberry high tunnels for Neopamera bilobata Say (Hemiptera: Rhyparochromidae) control

Abstract: Strawberry is affected by several pests and diseases. Neopamera bilobata is an emerging pest that has been reported by several strawberry growers, usually associated with catfacing symptoms in fruits. We evaluated intercropping garlic or Chinese chives on N. bilobata populations on strawberry crops grown in high tunnels in two experiments. In the first experiment, we evaluated N. bilobata populations on strawberry intercropping with garlic plants (three densities: 8, 16, 24 GP - garlic plant per plot) on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Our data show a potential use of Chinese chives and chives for TSSM control, and studies with other pests may be conducted. A previous study showed Chinese chives in intercropping reduced Neopamera bilobata Say, an emerging pest of strawberry [7]. In a chemical characterization study, it was revealed that dimethyl disulphide, allyl methyl disulfide, and dimethyl trisulphide were the major essential oils present in Chinese chives and dipropyl disulfide, dipropyl trisulfide, and methyl propyl trisulfide in chives composition [35].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our data show a potential use of Chinese chives and chives for TSSM control, and studies with other pests may be conducted. A previous study showed Chinese chives in intercropping reduced Neopamera bilobata Say, an emerging pest of strawberry [7]. In a chemical characterization study, it was revealed that dimethyl disulphide, allyl methyl disulfide, and dimethyl trisulphide were the major essential oils present in Chinese chives and dipropyl disulfide, dipropyl trisulfide, and methyl propyl trisulfide in chives composition [35].…”
Section: Discussionmentioning
confidence: 98%
“…Intercropping may be included as one of the tools for integrated pest management of strawberry pests. As Chinese chives and garlic were already tested as an intercrop for the control of N. bilobata, a new pest species in Brazilian strawberry crops [7], this approach may be tested for other pests, such as Drosophila suzukii Matsumura and Duponchelia fovealis Zeller, species with a high potential for causing damage to strawberry. Future studies may also combine sustainable management practices, such as the reduction of the source of fertilization to optimal levels [38,39], use of low impact insecticides and entomopathogenic agents [38,40,41], and incorporation of plants that maintain or enhance natural enemy populations in the crop production landscape [42,43], to build an organic strawberry production protocol that may be used even for conventional strawberry growers or incorporated into others IPM crop protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a LER index above one was obtained for the intercropping system, which indicated that there is greater efficiency in the use of land than with monocrops. Garlic was initially proposed and succeed as an intercropping plant for pest reduction in strawberry crops (HATA et al, 2016;HATA et al, 2018) and may provide an additional source of income without increased inputs (except garlic bulbs seeds). To produce garlic in a strawberry intercropping system, the same crop management was used.…”
Section: Discussionmentioning
confidence: 99%
“…Say (Heteroptera, Rhyparochromidae) Up to 64% decrease in N. bilobata population on strawberry plants Hata et al (2018) Glycine max (L.) Merr. Himanen et al (2015) practical pest management situations.…”
Section: Neopamera Bilobatamentioning
confidence: 99%